EVALUASI PELAKSANAAN PEMBELAJARAN PRAKTEK KAYU PROGRAM STUDI TEKNIK KONSTRUKSI KAYU JURUSAN BANGUNAN SMK NEGERI 1 KEC. GUGUAK KAB. LIMA PULUH KOTA - 468-477 , Anggi Yonara (CIVED, 2015)
ABSTRACK This research is motivated that poor implementation of learning practices wooden Wood Construction Engineering Program Department of Building SMK Negeri 1 subdistrict Guguak District Fifty Cities. Therefore, the purpose of this study was to determine how the quality of practice teaching in SMK Negeri 1 timber, based on students' perceptions about learning methods, the implementation of the learning process and the means of learning practices This research is the evaluation, and the sample population in this study, the students of class XI TKK and class XII students TKK Department of Building SMK Negeri 1 Guguak District of the City District Fifty amounted to 12 and 20 students. Techniques in data collection using questionnaire using a Likert scale. Analysis using the percentage formula and the formula mean. The results of this study indicate that based on the students' perceptions about teaching methods used by teachers to walk with enough categories, the implementation of the learning process that teachers do run with enough categories, while the means of learning practices is also considered sufficient. Keywords: evaluation, implementation, learning wooden practice